A complex case of dual ocular pathologies in an adolescent: a diagnostic challenge - Mohd Noor, Syamin; Jabbari, Aidila Jesmin; Rosli, Abdul Hadi (Springer Nature, 2025)
Clinical manifestations of ocular disease may overlap, and although rare, patients may suffer from more than one disease consecutively, complicating the diagnostic process. This case highlights an uncommon presentation of Vogt-Koyanagi-Harada (VKH) disease following Bartonella henselae infection in a 15-year old girl. She presented with a two-month history of bilateral eye blurring of vision, associated with a throbbing headache. Examination revealed the presence of anterior uveitis with bilateral optic disc swelling and partial macular star. Diagnosis of bilateral ocular bartonellosis with neuroretinitis was made based on positive serology. Following treatment of oral azithromycin for six months, her vision improved with resolution of neuroretinitis. Eleven months later, she presented again with blurred vision in both eyes. Fundus examination revealed bilateral optic disc swelling and retinal pigmentary changes with right exudative macular detachment. The investigations were negative for an infective or inflammatory origin. Fundus fluorescein angiography (FFA) showed minimal pinpoint leakage in the early phase and a moth-eaten appearance in the late phase. These findings led to the diagnosis of chronic Vogt-Koyanagi-Harada (VKH) disease. This case emphasizes the importance of having a high degree of suspicion to ensure correct diagnosis and management of patients.